2009
DOI: 10.25011/cim.v32i2.6031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estrogens on oxidative protein damage in plasma and tissues in ovariectomised rats

Abstract: Purpose: To assess estrogen-related changes in the redox status of the brain and liver proteins as well as the systemic oxidative stress in ovarectomised (OVX) rats Methods: Twelve-week-old, sexually mature female Sprague–Dawley rats (200-250g) were randomly divided into four groups: The following treatment combinations were administrated daily to all in 0.05 ml 96% ethanol solution by gastric gavage. (1) Sham operation (2) OVX rats (3) OVX rats [0.02 mg/kg/day of 17?-estradiol (E2) and 0.01 mg/kg/day of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 28 publications
3
27
0
1
Order By: Relevance
“…In the present study, dietaries once heated and five times heated palm and soy oil for four months had significantly increased the plasma lipid peroxidation in ovariectomized female rats. The result is in agreement with other studies which also reported that in ovariectomized-induced estrogen deficiency, an increase in oxidative stress accompanied by a reduction in antioxidant status was seen [57][58]. A study by Sánchez-Rodríguez [59] had recently found that menopause could be one of the main risk factors for oxidative stress.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, dietaries once heated and five times heated palm and soy oil for four months had significantly increased the plasma lipid peroxidation in ovariectomized female rats. The result is in agreement with other studies which also reported that in ovariectomized-induced estrogen deficiency, an increase in oxidative stress accompanied by a reduction in antioxidant status was seen [57][58]. A study by Sánchez-Rodríguez [59] had recently found that menopause could be one of the main risk factors for oxidative stress.…”
Section: Discussionsupporting
confidence: 82%
“…e 17β-estradiol + drospirenone group lost more weight than the 17β-estradiol + norhisterone acetate group, likely due to the natriuretic properties of drospirenone (Table 1). e information in Table 1 is identical to that included in a previous study by our group [11].…”
Section: Resultssupporting
confidence: 62%
“…Parameters and data regarding oxidative stress and brinolysis in the present study were derived from a previous study by our group [11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to this unique feature, membrane proteins of aging erythrocytes are primary targets for ROS and RNS 14,15 . Erythrocyte membrane protein carbonyl content was found to increase in an age-related pattern indicating an increase in oxidative protein damage in elderly subjects (Fig.…”
Section: Resultsmentioning
confidence: 99%